Interaction between turbidity currents and a contour current – A rare example from the Ordovician of Shaanxi province, China - Li, Hua; van Loon, A.J. [lpar]Tom[rpar]; He, Youbin (Geologos, 2019)
The silty top parts of graded turbidites of the Late Ordovician Pingliang Formation, which accumulated along the southern margin of the Ordos Basin (central China), have been reworked by contour currents. The reworking of the turbidites can be proven on the basis of paleocurrent directions in individual layers: the ripple-cross-bedded sandy divisions of some turbidites show transport directions consistently into the downslope direction (consistent with the direction of other gravity flows), but in the upper, silty fine-grained division they show another direction, viz. alongslope (consistent with the direction that a contour current must have taken at the same time). Both directions are roughly perpendicular to each other. Moreover, the sediment of the reworked turbidites is better sorted and has better rounded grains than the non-reworked turbidites. Although such type of reworking is well known from modern deep-sea environments, this has rarely been found before in ancient deep-sea deposits. The reworking could take place because the upper divisions of the turbidites involved are silty and consequently relatively easily erodible, while the contour current had locally a relatively high velocity – and consequently a relatively large erosional capability – because of confinement within a relatively narrow trough.